ANALISIS PENERAPAN JUST IN TIME DALAM MENINGKATKAN EFESIENSI PRODUKSI PADA PT. TRI STAR MANDIRI - Sultan Sarda; Muttiarni Muttiarni; Nur Afmi (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2019)
This type of research is a case study. Data collection is done by interview method, and documentation. The analysis method used is qualitative descriptive analysis, which is a method that emphasizes deeper aspects of understanding deeply the problem rather than looking at problems for generalization research.The results of his research are in the cost of storage before the application of the Just In Time System, the cost of storing the raw material is Rp. 32,086,720 while the Storage Cost after the Application of the Just In Time System, the cost of storing the raw material is Rp. 16,043,360 Then it can reduce the cost of storing raw materials (material) of Rp. 16,043,360 So that it can increase production productivity. However, in measuring the overall time required in the production process of concrete mix is said to be inefficient because the time needed before using JIT is smaller than after using JIT so it is not efficient in increasing the productivity of the company at PT. Tri Star Mandiri.